2021
DOI: 10.2174/1381612826666200519113752
|View full text |Cite
|
Sign up to set email alerts
|

Datura metel: A Review on Chemical Constituents, Traditional Uses and Pharmacological Activities

Abstract: : Datura metel (Solanaceae) which is commonly known as thorn’s apple, Indian apple or devil’s trumpet isan annual herb of temperate zones which is distributed all over the world. D. metel belongs to the family solanaceae. From longer period of time (37 A.D), species of this family had therapeutic uses. This article is based on the review of different scientific backgrounds and studies regarding the traditional uses, phytochemistry, biochemical constituents and pharmacological uses of D. metel. This review is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…MTT assay was accomplished by following an already established protocol Maqbool et al [16]. In brief, Datura metel plant ethanol and n-hexane extracts were applied in increasing concentrations (10,25,50, 100, 200ug/mL) on HepG2 liver cell line and BHK cell lines via MTT (3-(4,5-dimethylthiazol-2-yl)-2,5diphenyl tetrazolium bromide) assay on plates of 96 wells for 72 h. A PBS (phosphate buffer saline) was used to wash the cell's monolayer. Samples without extracts served as control.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…MTT assay was accomplished by following an already established protocol Maqbool et al [16]. In brief, Datura metel plant ethanol and n-hexane extracts were applied in increasing concentrations (10,25,50, 100, 200ug/mL) on HepG2 liver cell line and BHK cell lines via MTT (3-(4,5-dimethylthiazol-2-yl)-2,5diphenyl tetrazolium bromide) assay on plates of 96 wells for 72 h. A PBS (phosphate buffer saline) was used to wash the cell's monolayer. Samples without extracts served as control.…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Plant-derived chemicals are typically nontoxic and more tolerated to normal human cells [9]. Datura metel is a medicinal plant with a long history in medicine and is considered to work as an antioxidant, apoptotic, and anti-proliferative agent [10]. Datura metel L. is an important therapeutically active genus of family Solanaceae.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant capacity of leaf extracts in different solvents, estimated by various in vitro methods, including hydroxyl radical scavenging activity, DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging activity, superoxide radical scavenging activity, β-carotene bleaching activity, and reducing power assay, revealed that chloroform extract of leaves possessed maximum concentration-dependent antioxidant activity [ 42 , 43 ]. The IC 50 value of methanolic and hydroalcoholic seed extracts of D. metel recorded using the DPPH model showed that hydroalcoholic extract possesses slightly higher antioxidant activities (IC 50 of 25.78 µg/mL) than methanolic seed extract (IC 50 of 28.34 µg/mL) [ 7 , 42 ].…”
Section: Pharmacological Activity Of Daturamentioning
confidence: 99%
“…Investigations on Wistar albino rats using the excision wound model demonstrated a positive correlation between the concentration of D. fastuosa ethanol extracts and woundhealing activities [8,64], examined based on several parameters, including the percentage of wound closure, the meantime for epithelization, hydroxyproline, DNA, and protein level. It was observed that D. fastuosa extracts (10% w/w) in the form of ointment possessed significant wound-healing capacity as compared to the standard Nitrofurazone ointment (0.2% w/w) [7,64].…”
Section: Cellular Protective and Wound-healing Effectsmentioning
confidence: 99%
See 1 more Smart Citation